Sistem Informasi Manajemen Gaji Pegawai Berbasis Web pada Koperasi Abadi Sejahtera Bulukumba - Anisha_isnul* Utami Putri; Adi Candra; Perawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to (1) design a web-based Employee Payroll Management Information System and (2) implement a web-based Employee Payroll Management Information System. The research method used was Research and Development (R&D) with the Waterfall development model, which consists of the following stages: (1) requirements analysis, (2) system design, (3) implementation, (4) testing, and (5) maintenance. Based on the results of the study, several conclusions can be drawn: (1) The Web-Based Employee Payroll Management Information System at Koperasi Abadi Sejahtera Bulukumba was designed using the Unified Modeling Language (UML), consisting of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system was developed using the PHP programming language and MySQL database and tested using the Black Box testing method. (2) The results of system validation conducted by two expert validators obtained a validity score of 1.00, indicating a high level of validity. This result shows that the system has good quality and attractiveness. User responses to the system were categorized as very good, with an assessment percentage of 92%, indicating that the system is feasible for use.